The Impacts of Minimum Wage Implementation in Malaysia: An Update - Eden, Dzulzalani (2016)
Minimum wage has been implemented in Malaysia in 2013 to address market failure in wage determination among low wage earners. This new mechanism has changed the labour market in Malaysia in terms of wage settings from one that is based on market forces to a state regulated floor wage determination in all sectors of the economy. This policy was aimed to uplift the standard of living of low-paid employees without causing any friction on the prevailing labour market. The thrust of this new policy is twofold. While the wage rate was set at above the rate to reflect a decent standard of living among the low wage earners, it was also set within firm's ability to pay based on the prevailing median wage.